The Effect of ESG Practices on Profitability Through Liquidity and Financial Constraints as Moderating Variables - Entis Sutisna; Kautsar Riza Salman (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to examine the impact of corporate involvement in activities related to the environmental, social, and governance on profitability performance. In addition, this study also examines the moderating effect of liquidity and financial constraints on the relationship between ESG practices and profitability performance. The objects of the study were 43 companies listed on the Jakarta Islamic Index 70 (JII70) and the SRI KEHATI index in the 2021-2023 period. The number of data observations was 129 data and was analyzed using Eviews software version 13. The results of the study show that corporate involvement in ESG activities has an impact on decreasing profitability performance during the study period and these results confirm the role of agency theory. The results of the study also show that financial constraints can strengthen the relationship between ESG practices and profitability performance. Conversely, liquidity cannot moderate the relationship between ESG practices and profitability performance. The theoretical implication from the perspective of agency theory is to strengthen the role of agency theory in explaining the impact of ESG on profitability in the short term. Practical implications for companies are related to the importance of the existence of activities related to ESG, although in the short term it reduces profitability, the long-term impact fosters a positive image of the company in the community.